Analysis Of Factors Affecting Labour Absorption In South Sumatra Province 2008-2022 - Lisa Hermawati; Andri Irawan (UNIVED Press, 2024)
The research aimed to determine the influence of the Minimum Wage and Education Level on Labor Absorption in South Sumatra Province 2008-2022 partially and simultaneously. This research was quantitative in nature with secondary data obtained from BPS South Sumatra Province with total time series data for 15 years 2008-2022. The method used was multiple linear regression. The data processing process was carried out with the help of a computer application, namely the SPSS program. The independent variables in this research were Minimum Wage (X1) and Education Level (X2) then the dependent variable was Labor Absorption (Y). The research results showed that simultaneously the Minimum Wage (X1) and Education Level (X2) variables influenced the Labor Absorption (Y) of South Sumatra Province in 2008-2022. Meanwhile, partially the Minimum Wage variable (X1) had a positive and significant influence on the Labor Absorption (Y) of South Sumatra Province in 2008-2022, and the Minimum Wage variable (X2) had a positive and significant influence on the Labor Absorption (Y) of South Sumatra Province 2008-2022. The coefficient of determination showed that the contribution of the Minimum Wage (X1) and Education Level (X2) in South Sumatra Province was 98.2%, while the remaining 1.8% was caused by other factors not examined in this research model.